Geophysical methods reveal a subsurface historic wastewater tunnel exposed by a sinkhole: a case study in Bandung City, Indonesia - Parnadi, Wahyudi Widyatmoko; Warsa, Warsa; Nailufar, Mira; Jubaedah, Neng Endah; Ruchimat, Acep (Journal of Degraded and Mining Lands Management, 2025)
Bandung City, the capital of West Java Province in Indonesia, has changed its physical face rapidly due to the many constructions of office buildings, hotels, and other facilities until now. To avoid the instability of existing buildings and for building construction in the future, knowledge of the subsurface conditions in the city must be enhanced. A sudden soil collapse in the yard of the PAG Building occurred in early 2018 and resulted in a sinkhole with a diameter of 5 m, which revealed a historic wastewater tunnel structure in the subsurface. Non-invasive, low-cost, and time-effective geophysical methods to solve those problems are proposed. Ground-penetrating radar (GPR) and Electrical Resistivity Tomography (ERT), widely applied to identify artificial objects underground, came to be used for these purposes. A research to know the suitability of both methods for application began with numerical simulation, followed by field measurement on 4 GPR and ERT lines and analysis of each method. The results show that GPR data, through both numerical and field data,  could identify and locate the tunnel in a radargram due to its hyperbola shape, whereas ERT data provided the property contrast between the tunnel and its host. The results suggest that GPR and ERT techniques are effective for revealing water tunnels in the study area with a maximum depth of 1.8 m and a 65% reduction in size. These findings can be used as a guide to using both methods to reveal the water tunnel network in the central part of Bandung City for sustainable urban planning.